Characteristics of cases needing advanced treatment for intractable Posner–Schlossman syndrome - Maruyama, Kazuichi (BMC Ophthalmol, 2017)
BACKGROUND: In Posner-Schlossman syndrome (PSS), which is characterized by recurrent unilateral attacks of ocular hypertension. Surgical treatment is sometimes necessary because intraocular pressure (IOP) cannot be controlled with anti-glaucoma medications. To identify the clinical features of Posner–Schlossman syndrome (PSS) indicative of the need for intraocular pressure (IOP)-controlling surgery. METHODS: This study was a retrospective case-series analysis of the clinical charts of 33 patients diagnosed with PSS, who underwent surgery to control IOP or received medication only. Various clinical factors were compared between the surgical and medication groups. RESULTS: The surgical group had a higher corneal endothelial cell (CEC) density loss (p < 0.05), higher maximum IOP (p < 0.01), greater visual field loss (p < 0.01) and higher positive number for cytomegalovirus (CMV) (p < 0.001) than the non-surgical group. Eighteen of the 33 patients had a high CEC reduction ratio. Of these 18, 16 required glaucoma surgery. CONCLUSIONS: PSS patients with a higher CEC reduction ratio, higher maximum IOP, greater visual field loss and higher positive number for CMV in the aqueous humor tended to be more likely to require progressive treatment, such as glaucoma surgery. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12886-017-0438-y) contains supplementary material, which is available to authorized users.